Pengaruh Kinerja Keuangan terhadap Harga Saham Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Periode 2019–2021 - Yulianto, Yocelyn (Jurnal KIAFE, 2025)
This study examines the effects of financial performance on stock prices in food and beverage companies listed on the Indonesia Stock Exchange during the 2019–2021 period. The study employs a quantitative causal approach using secondary data obtained from audited annual reports and financial statements. The sample was selected through purposive sampling and consisted of 132 firm-year observations. Financial performance was represented by the Current Ratio, Debt-to-Equity Ratio, Return on Assets, Total Asset Turnover, growth in Earnings per Share, and Price-to-Book Value. Data were analyzed using panel-data regression with EViews version 12. Based on the Chow, Hausman, and Lagrange Multiplier tests, the random-effects model was selected as the most appropriate estimation model. The results show that Return on Assets, Total Asset Turnover, and Price-to-Book Value have positive and significant effects on stock prices. The Current Ratio has a positive but insignificant effect, while the Debt-to-Equity Ratio and growth in Earnings per Share have negative but insignificant effects. Simultaneously, all six financial-performance indicators significantly affect stock prices. The adjusted coefficient of determination is 35.54%, indicating that the model explains 35.54% of the variation in stock prices.